PERAN TEKNOLOGI FINANSIAL DALAM MEMBANTU MAHASISWA MENGATASI KENDALA PEMBIAYAAN PENDIDIKAN - Riinawati, Riinawati (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to explore how financial technology (fintech) services are utilized by university students to overcome educational financing challenges and how this impacts their academic continuity. Using a qualitative approach, data were gathered through in-depth interviews with students from diverse academic programs and economic backgrounds. The results reveal that students' understanding of fintech is mostly shaped by exposure through social media and peer networks, with varying levels of awareness regarding its functions and legality. Key motivating factors for using fintech include urgent financial needs for tuition, delays in paying educational fees, and the convenience and speed offered compared to traditional financial institutions. While fintech provides a flexible alternative for educational funding, some students experience psychological stress due to debt burdens and limited skills in managing their finances. On the other hand, several students feel supported and financially more independent through fintech use. This research highlights the importance of collaboration among universities, students, and fintech providers to promote financial literacy and to ensure secure and sustainable educational financing systems.